Evaluation of Free Radical Scavenging Activity of Iridoid Aucubigenin and its Glycoside - Li1, Yang; Chen2, Lei; Qiao3, Haiou; Wang3, Minjuan; Zhao1, Ye (Asian Journal of Chemistry, 2014)
The iridoid aucubigenin and its glycoside aucubin have been investigated for their in vitro free radical scavenging activity. Various methods, such as the scavenging activities towards DPPH radical, superoxide anion radical and hydroxyl radical, were efficiently established. The results showed that both compounds exhibited significant differences in free radical scavenging activity.